Integrating Electric Vehicle Technology into Automotive Education Curricula in Colleges of Education in Nigeria: Challenges and Opportunities - Gwana, Bawa Haruna; Sule, Samaila Yerima (Lembaga Yasin AlSys, 2024)
The main purpose of the study was to integrate electric vehicle technology into Automotive Education Curricula in Colleges of Education in Nigeria with focus on the challenges and opportunities. The study which adopted a descriptive survey research design was conducted in northeast Nigeria and had three research questions. The population of the study was 395 comprising 248 lecturers in Automobile Technology Education from 8 Colleges of Education in the Northeast and 147 industry professionals whose industries are registered with the Corporate Affairs Commission as well as the Ministry of Commerce and Industries in the various states of the Northeast. The study adopted simple random sampling technique which Krejcie and Morgan (1970) sample size table and 191 respondents were selected. A structured questionnaire developed by the researcher titled: